Internal Structure and Current Evolution of Very Small Debris-Covered Glacier Systems Located in Alpine Permafrost Environments - Bosson, Jean-Baptiste; Lambiel, Christophe (Frontiers in Earth Science, 2016)
This contribution explores the internal structure of very small debris-covered glacier systems located in permafrost environments and their current dynamical responses to short-term climatic variations. Three systems were investigated with electrical resistivity tomography and dGPS monitoring over a 3-year period. Five distinct sectors are highlighted in each system: firn and bare-ice glacier, debris-covered glacier, heavily debris-covered glacier of low activity, rock glacier and ice-free debris. Decimetric to metric movements, related to ice ablation, internal deformation and basal sliding affect the glacial zones, which are mainly active in summer. Conversely, surface lowering is close to zero (-0.04 m yr-1) in the rock glaciers. Here, a constant and slow internal deformation was observed (c. 0.2 m yr-1). Thus, these systems are affected by both direct and high magnitude responses and delayed and attenuated responses to climatic variations. This differential evolution appears mainly controlled by (1) the proportion of ice, debris and the presence of water in the ground, and (2) the thickness of the superficial debris layer.